2020
DOI: 10.1021/acsami.9b18426
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Porous SnO2 Nanoparticle-Anchored Polypyrrole Nanotubes as a High-Efficient Sulfur/Polysulfide Trap for High-Performance Lithium–Sulfur Batteries

Abstract: Conductive supports could improve the electrical conductivity of the electrode in lithium–sulfur (Li–S) batteries but suffer from the shuttle effect originated from the polysulfide dissolution, while the hydrophilic metal oxides could avoid the shuttle effect but with poor conductivity. Herein, a facile approach was developed to fabricate hierarchically porous tin oxide (SnO2) nanoparticle-anchored tubular polypyrrole (T-PPy) as a sulfur host, in order to integrate the advantages of conductive supports and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The S@Co 3 O 4 and S@Co 3 O 4 /PPy cathode showed an initial discharge specific capacity of 909.2 and 1094.9 mAh g À1 , respectively, and maintained a capacity of 150.1 and 370.6 mAh g À1 after 1000 cycles at 0.5 C, respectively. Wei et al [133] anchored the tin oxides (SnO 2 ) nanoparticles onto the tubular PPy (T-PPy) surface and then sulfur deposited on them formed the S/(T-PPy)@SnO 2 composite. Because of the chemical bond between SnO 2 and lithium polysulfides, the hierarchically porous SnO 2 was mainly used as an effective lithium polysulfide trap to reduce their ''shuttle effect".…”
Section: S/se With Ppy and Polar Materialsmentioning
confidence: 99%
“…The S@Co 3 O 4 and S@Co 3 O 4 /PPy cathode showed an initial discharge specific capacity of 909.2 and 1094.9 mAh g À1 , respectively, and maintained a capacity of 150.1 and 370.6 mAh g À1 after 1000 cycles at 0.5 C, respectively. Wei et al [133] anchored the tin oxides (SnO 2 ) nanoparticles onto the tubular PPy (T-PPy) surface and then sulfur deposited on them formed the S/(T-PPy)@SnO 2 composite. Because of the chemical bond between SnO 2 and lithium polysulfides, the hierarchically porous SnO 2 was mainly used as an effective lithium polysulfide trap to reduce their ''shuttle effect".…”
Section: S/se With Ppy and Polar Materialsmentioning
confidence: 99%
“…[ 108 ] Under the synergistic effect of H‐TiO x and PPy, the composite delivered capacity retention rate of 59.4% after 1000 cycles at 1C. Wei et al reported a facile approach to synthesis the SnO 2 @tubular PPy (T‐PPy@SnO 2 ) as the host of S. [ 109 ] The T‐PPy nanotubes with large surface area could accommodate the volume expansion of S, and anchor polysulfides to exhibit the long‐cycle stability with a high capacity retention rate of 75% after 500 cycles at 1C.…”
Section: Coatingmentioning
confidence: 99%
“…The conductivity of SnO 2 is better than that of most other oxides in the porous structure. [37] SnO 2 -decoration of the porous nanomaterials has aroused spreading interest. 2D nanomaterials benefit from its ultra-thin layered structure, large specific surface area, excellent photoelectric and mechanical properties, easy interface transmission and short diffusion, displaying very suitable features for being used in energy storage devices.…”
Section: Application Of Sno 2 In Cathodementioning
confidence: 99%
“…Among them, SnO 2 nanoparticles with the characteristics of environmental friendliness, easy preparation, chemical stability, and high energy density are widely concerned. [13,14,37] As a Sn-based compound, SnO 2 inherits the unique performance advantages of the Sn element in the following section: 1) Sn-based materials with high conductivity has been widely used in the electrochemical field because of their excellent ability to accommodate Li + . 2) Sn is an ecofriendly element with low biological toxicity and no pollution to the environment.…”
Section: Introductionmentioning
confidence: 99%